Bladder Cancer Tissue-Based Biomarkers - Francesco Soria, Marta Sanchez-Carbayo, Natalya Benderska-Söder , Bernd J Schmidz-Dräger, Stefania Zamboni, Marco Moschini, Anirban P Mitra, Yair Lotan (Société Internationale d’Urologie Journal, 2021)
This review aims to provide a practical update regarding the current role of tissue-based biomarkers in bladder cancer. Their prognostic and predictive role both in non-muscle-invasive (NMIBC) and in muscle-invasive disease (MIBC) has been reviewed with particular focus to their use in clinical practice. In summary, the literature on the prediction of disease recurrence in NMIBC is inconclusive, and there is little information on prediction of response to intravesical bacillus Calmette-Guérin (BCG). Concerning disease progression, external prospective validation studies suggest that FGFR3 mutation status and gene signatures may improve models that are based only on clinicopathologic information. In MIBC, tissue-based biomarkers are increasingly important, since they may predict the response to systemic chemotherapy and immunotherapy. In particular, the advent of molecular characterization promises to revolutionize the paradigm of decision-making in the treatment of MIBC. Molecular subtyping has been shown to improve the prediction of pathological stage at RC and to predict the response to systemic chemotherapy and immunotherapy. However, external and prospective validations are warranted to confirm these preliminary findings. Several different tissue-based biomarkers such as PD-1/PD-L1 expression, tumor mutational burden, and the analysis of tumor microenvironment, may in future play a role in selecting patients for systemic immunotherapy. However, to date, no pretreatment recommendations can be definitively made on the basis of any molecular predictors.In conclusion, despite the potential of tissue-based biomarkers, their use in bladder cancer should be limited to experimental settings.